DAUR ULANG AIR LIMBAH (WATER RECYCLE) DITINJAU DARI ASPEK TEKNOLOGI, LINGKUNGAN DAN EKONOMI - Said, Nusa Idaman (Jurnal Air Indonesia, 2006)
In line with fast growth of populations in urban area the discharged waste water from daily activities have caused contamination of ground water and also surface water. Unbalance between distribution of source and usage of water have caused unbalance between supply and demand. Therefore, new innovation in the case supply of raw water has come to important attention. One of the alternatives which getting much attention in many state in world is to use recycle wastewater especially municipal wastewater as one source of raw water for water supplySeveral things which need to be paid attention in the case of usage of recycle wastewater are consistency of the treated water quality as according to enabled condition. In usage of recycle wastewater to be used as clean water supply there is several categorize of contaminant which must be paid attention peculiarly namely for example organic contaminant including pesticide, pathogenic bacteria, parasite, virus and also heavy metal contaminant for example mercury, lead, chrome, cadmium etc. Therefore the treatment process must be done neglectlessly with control of quality which able to be justified.One of the concept for processing of urban wastewater to be made clean water is use combination of primary treatment, secondary treatment with biological process continued by advanced treatment by physico-chemical process for example covering clarification process, nutrient removal, recarbonation, filtration, adsorption with activated carbon, ion exchange process, and also demineralization with process of reverse osmosis and also ozonization and chlorination. With these processes combination can treat wastewater yield treated water with quality of as drinking water.This paper explained some example of wastewater treatment process for recycle wastewater which have been applicated in some state. One of the example of wastewater recycle process using combination of biological process continued with ultra filtration process, reverse osmosis process, and disinfection by ultraviolet, and also pH control such as those which have been conducted by NEWATER Factory, Singapore.Ã‚Â Kata Kunci : Daur ulang, air limbah, teknologi, lingkungan.